Language Works 3(2) - Thøgersen, Jacob; Nguyen, Michael Hai; Sørensen, Søren Sandager; Muth Andersen, Elisabeth; Dakwar, Julia Rytter (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
Welcome to this the fifth edition of the Danish student journal of linguistics known as Language Works – Sprogvidenskabeligt Studentertidsskrift